2003
DOI: 10.1248/bpb.26.19
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Intracellular Glutathione by Low-Dose .GAMMA.-Ray Irradiation Is Mediated by Transcription Factor AP-1 in RAW 264.7 Cells.

Abstract: The mechanism of the elevation of intracellular glutathione induced by low-dose g g-rays was examined in RAW 264.7 cells. The expression of mRNA for g g-glutamylcysteine synthetase (g g-GCS) increased soon after g g-ray (0.5 Gy) irradiation, and peaked between 3 h and 6 h post-irradiation. A dose of 0.25 to 0.5 Gy was optimum for induction of g g-GCS mRNA expression at 3 h post-irradiation. The effect of inhibitors of activator protein-1 (AP-1) and nuclear factor k kB (NF-k kB) on the radiation-induced g g-GCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…These kinases further activate different redox-sensitive transcription factors like Nuclear Factor-kB (NF-kB) and Activating protein-1 (AP-1). The activation of these transcription factors result in the gene expression of various antioxidant defense proteins to overcome the effect of oxidative stress-mediated cellular damage (Kawakita et al 2003). However, our results are in contrast with earlier reports (Yamaoka et al 1991(Yamaoka et al , 1993, which showed a 20 -30% decrease in the lipid peroxidation levels in the rat brain and liver at radiation doses near 50 cGy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These kinases further activate different redox-sensitive transcription factors like Nuclear Factor-kB (NF-kB) and Activating protein-1 (AP-1). The activation of these transcription factors result in the gene expression of various antioxidant defense proteins to overcome the effect of oxidative stress-mediated cellular damage (Kawakita et al 2003). However, our results are in contrast with earlier reports (Yamaoka et al 1991(Yamaoka et al , 1993, which showed a 20 -30% decrease in the lipid peroxidation levels in the rat brain and liver at radiation doses near 50 cGy.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the glutathione level increased significantly (p50.05) at 25 cGy exposure both in lungs and liver suggesting its protective effect in these organs against radiation induced oxidative stress. The increased GSH levels might be due to an increase in the expression of mRNA for g-glutamylcysteine synthetase (g-GCS), a rate limiting enzyme in GSH synthesis , Kawakita et al 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5 0 -flanking region of the human GCLC gene (L39773) contains a consensus activator protein-1 (AP-1) site and several AP-1-like binding sites, which are also referred to as TRE (PMA-responsive element) or TRE-like elements (Mulcahy and Gipp, 1995;Mulcahy et al, 1997). Several studies suggest that the binding sites in this proximal region are critical to the upregulation of GCL transcription in response to a variety of agents inducing oxidative stress in humans (Sekhar et al, 1997;Rahman et al, 1998;Palomero et al, 2001), as well as other mammals, such as the rat (Yang et al, 2002) and mouse (Kawakita et al, 2003).…”
mentioning
confidence: 99%
“…Thus, mRNAs for glutathione-synthesis-related proteins in the mouse liver became elevated after low-dose γ -irradiation (Kojima et al, 1998). The low-dose-caused increase in intracellular glutathione in RAW-264.7 cells with its maximum between 3 and 6 hr after exposure was mediated by transcriptional regulation of the γ -glutamylcysteine synthetase gene, predominantly through the AP-1 binding site in its promoter (Kawakita et al, 2003). • Protection against high-dose induced chromosomal aberrations in human lymphocytes increased to a maximum about 4 hr after a conditioning low-dose low-LET irradiation; the protection also operated against other DNA damaging agents (Olivieriet al, 1984;Wolff et al, 1988).…”
Section: Adaptive Protection Responsementioning
confidence: 97%